Regioselective Functionalization of Purine Derivatives at Positions 8 and 6 Using Hindered TMP-Amide Bases of Zn and Mg - Crestey, François; Zimdars, Silvia; Knochel, Paul (Synthesis, 2013)
A broad range of purine derivatives were efficiently metalated at positions 8 and 6 using TMP-amide bases. This provided polysubstituted purines in good to very good yields after subsequent trapping of the zinc or magnesium intermediates with various electrophiles.
Keywords: purine derivatives; metalation; Negishi cross-coupling; magnesium; zinc